(untitled) (Journal of Libya for geographical studies, 2025)
Education is one of the fundamental services in human life, as it is a key indicator of human development. Progress and advancement in any field of life largely depend on the level of education. Consequently, the learner is more productive and creative than others, which highlights the necessity of focusing on education. This study aims to analyze the spatial distribution of primary education services in Al-Qasim City (one of the cities in Babil Governorate) for the school year 2023-2024. The research found that the city has 26 primary schools distributed across 7 residential neighborhoods out of a total of 20 neighborhoods, meaning that only 35% of neighborhoods are served, while 65% (equivalent to 13 neighborhoods) are underserved due to insufficient planning to accommodate population growth. This indicates a shortage in the number of existing schools, reflected by a student-to-school ratio of 576 students per school, which greatly exceeds the accepted standard of 360 students per school. According to this standard, an additional 16 schools are required beyond the current number. The student-to-teacher ratio is 25 students per teacher, and the student-to-class ratio is 40 students per class. Overall, these figures surpass the approved standards, indicating a significant deficit in the number of schools, along with an uneven distribution among neighborhoods. For instance, some neighborhoods are densely served, such as 7 schools in Al-Qadimah neighborhood and 8 schools in Al-Hussein neighborhood, while many neighborhoods lack schools altogether. Functional efficiency of educational services in Al-Qasim City can be achieved through two main measures: constructing new schools and redistributing schools more equitably to avoid concentration in certain areas. Additionally, the city suffers from a shortage of school buildings, resulting in double and triple shifts, which negatively impact the functional efficiency of education services.